Capturing Real Impacts: Environmental Peacebuilding Evaluation in the Middle East: Lessons Applicable Worldwide - Malkowsky, Charleen (Student Undergraduate Research E-journal!, 2019)
This research was conducted to close the knowledge gap relating to suitable evaluation methodologies for interdisciplinary approaches of Environmental Peacebuilding, covering not only intended but also unintended, unanticipated, positive and negative, short and long-term outcomes. Information was gathered on Middle Eastern case studies and from a global perspective, triangulating facts from literature reviews, expert-, NGO-, and beneficiary interviews, and a global expert survey. Findings clarify the complexity of internal and external, donor-based aspects, all indicating the need to fundamentally revise current evaluation structures to ensure effectiveness of projects. Moreover, a framework was developed to support practitioners in their monitoring and evaluation (M&E) activities.